The Contagion Effects of Sovereign Downgrades: Evidence from the European Financial Crisis - Corbet, Shaen (International Journal of Economics and Financial Issues, 2013)
This research examines the effects of sovereign downgrades on European financial markets between 2005 and 2012. Vector Autoregression (VAR) techniques are used to investigate the presence of contagion effects after a sovereign downgrade across equity indices, five year Credit Default Swaps (CDS) and ten year government bonds of the investigated European states. Sovereign downgrades are found to be associated with an increase in equity returns, and cause significant increases in the cost of insuring debt through CDS and the yield of government debt. The Greek and Irish downgrades are to found to have significant reverberations throughout European financial markets. German CDS spreads are found to increase when a European state is downgraded, signalling their use by investors as a barometer of European-wide defaults. Though credit rating agencies clearly missed the European sovereign crisis prior to 2007, their rating downgrades are still found to cause significant effects within European financial markets. Keywords: Sovereign ratings; VAR; contagion; financial crisis; stock markets. JEL Classifications: G01; G15